Accelerated hydrazone formation in charged microdroplets. (25th July 2016) - Bain, Ryan M.; Pulliam, Christopher J.; Ayrton, Stephen T.; Bain, Kinsey; Cooks, R. Graham
Abstract : Rationale: Electrospray ionization‐mass spectrometry (ESI‐MS) is an emerging tool for reaction monitoring. It can be accompanied by reaction acceleration in charged droplets. Methods: The time course of the bulk reaction of indoline‐2, 3‐dione with phenylhydrazine in methanol to produce 3‐(2‐ phenylhydrazono)indolin‐2‐one was monitored by ESI. Both nanoESI and electrosonic spray ionization (ESSI) were used for this study as representing two common forms of ionization for reaction monitoring. The effect on product yield of the distance the droplets travel between the source and the MS inlet was varied and product/starting material ratios were examined. Results: Product yield is dramatically increased by increasing the distance. At short distances reaction monitoring can be performed without acceleration and at greater distances reaction acceleration occurs. This distance effect over the course of the reaction roughly parallels the time dependence of the bulk‐phase reaction. Conclusions: Reaction acceleration in droplets is attributed to solvent evaporation leading to increased surface to volume ratios. An acceleration factor of 10 4, measured relative to the bulk reaction at short times, is readily achieved by simply increasing the droplet distance of flight showing that the same ionization source can be used to monitor reactions with or without acceleration. Copyright © 2016 John Wiley & Sons, Ltd.